PEMANFAATAN RECYCLED CONCRETE WASTE SEBAGAI ALTERNATIF BAHAN STABILISASI TANAH LEMPUNG UNTUK PENINGKATAN NILAI CALIFORNIA BEARING RATIO (CBR) - Fitridawati Soehardi; Marta Dinata; Hendri Rahmat; Marlaily Idris; Junaidi Junaidi (Racic : Rab Construction Research, 2025)
Clay soil has low bearing capacity and high plasticity, which requires stabilization efforts to improve its strength. This study aims to analyze the effectiveness of Recycled Concrete Waste (RCW) as an alternative stabilizing material in improving the California Bearing Ratio (CBR) value of clay soil. The research was conducted through a series of laboratory tests, including physical property analysis, Standard Proctor compaction tests, and CBR tests under RCW mixture variations of 0%, 5%, 10%, 15%, and 20%, both in unsoaked and soaked conditions. The results indicate that the Optimum Moisture Content (OMC) increased from 1.65% to 18.1%, while the Maximum Dry Density (MDD) decreased from 19.8 g/cm³ to 17 g/cm³, and slightly increased to 17.5 g/cm³ at 15% RCW content. The CBR value showed a significant improvement, increasing from 4.6% to 15% under unsoaked conditions and from 3.30% to 12.80% after soaking. It can be concluded that the optimum RCW content of 20% effectively enhances the soil’s bearing capacity and water resistance while offering an environmentally friendly solution for subgrade stabilization in road construction